Extraosseous Thoracic Foraminal Osteoblastoma: Diagnostic Dilemma and Management with 3 Year Follow-Up - Shailesh Ramakant Hadgaonkar; Ashok Kumar Shyam; Kunal Chandrakant Shah; Ketan Shripad Khurjekar; Parag Kantilal Sancheti (Asian Spine Journal, 2014)
Osteoblastomas are bone forming lesions arising mainly from posterior elements of the vertebra. They are commonly encountered in the cervical and lumbar regions. We present a case of a thoracic osteoblastoma which is extra osseous and is not communicating with any part of the vertebra present intraforaminally. This is a rare presentation of an osteoblastoma. Imaging studies do not accurately diagnose the osteiod lesion. The size of the lesion and cortical erosion seen on the computed tomography scan help in differentiating the osteoid osteoma and osteoblastoma, but they are less sensitive and specific. Thus a histopathology is the investigation of choice to diagnose the osteoblastoma. Early and adequate removal of mass prevents malignant transformation, metastasis, and recurrence. In our case we excised the pars interarticularis unilaterally, removed the osteoid mass intact, and performed unilateral instrumented fusion. There was no recurrence and solid fusion was seen at 3 years follow up.